2011
DOI: 10.1002/micr.20916
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative color Doppler sonography in the elevation of anterolateral thigh flap

Abstract: There are currently multiple imaging techniques available for planning perforator flap harvest. Some studies demonstrated the superiority of computed tomographic angiography (CTA) over the other options for the preoperative mapping in the perforator flaps because it could evaluate the perforators more precisely.1 Nevertheless, CTA has a disadvantage that it cannot be used in real time and provide real-time feedback during harvesting flap. Color Doppler sonography is another effective tool for surgical planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…High‐resolution CCDS guided vascular flow imaging has proven as a potent instrument for microsurgeons in evaluating perforator vessels to simplify the design of perforator flaps in reconstructive surgery. Within the last few years, it has developed impetus and may spread faster than other modalities for detection and assessment of microvessels required for preoperative microvascular flap planning (Debelmas, Camuzard, Aguilar, & Qassemyar, 2018; Dorfman & Pu, 2014; Ensat et al, 2012; Feng et al, 2016; Gravvanis et al, 2010; Saito et al, 2011; Su et al, 2013). Anatomic and hemodynamic information may be provided in real‐time imaging by CCDS of both vascular structures of the donor and recipient sites of flap reconstructions (Gravvanis, Petrocheilou, Tsoutsos, Delikonstantinou, & Karakitsos, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution CCDS guided vascular flow imaging has proven as a potent instrument for microsurgeons in evaluating perforator vessels to simplify the design of perforator flaps in reconstructive surgery. Within the last few years, it has developed impetus and may spread faster than other modalities for detection and assessment of microvessels required for preoperative microvascular flap planning (Debelmas, Camuzard, Aguilar, & Qassemyar, 2018; Dorfman & Pu, 2014; Ensat et al, 2012; Feng et al, 2016; Gravvanis et al, 2010; Saito et al, 2011; Su et al, 2013). Anatomic and hemodynamic information may be provided in real‐time imaging by CCDS of both vascular structures of the donor and recipient sites of flap reconstructions (Gravvanis, Petrocheilou, Tsoutsos, Delikonstantinou, & Karakitsos, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Each method features different advantages and limitations. Comparing diagnostic imaging with intraoperative findings in free flap surgery commonly shows differing results concerning perforator size, location, anticipated course, and relation to surrounding structures (Hallock, ; Saito et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…17 CCDS has quickly gained momentum and seems to spread faster than other diagnostic modalities for perforator evaluation. 2,10,14,25,[27][28][29] Kehrer et al demonstrated that sensitivity of CCDS was 96.7% with an average distance from the true projection of EP to the CCDS skin marking of 2.45 AE 1.90 mm (range: 0-6 mm). 19 All perforators detected by CCDS and confirmed intraoperatively were sizable (!…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] However, comparing diagnostic imaging with intraoperative findings may show differing results concerning perforator size, location, anticipated course, and relation to surrounding structures. 13,14 Furthermore, most of the named diagnostic imaging tools present disadvantages in terms of invasiveness of techniques, costs or availability. 5,15 It was reported that 1.5 to 2.0% of all cancers in the United States may be attributable to the radiation from CT studies.…”
mentioning
confidence: 99%